2019
DOI: 10.1002/jmri.26936
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Hemodynamics of Autogenous Arteriovenous Fistulas With 4D Phase Contrast‐Based Flow Quantification MRI in Dialysis Patients

Abstract: Background Regular monitoring of autogenous arteriovenous fistulas (AVFs) for hemodialysis patients has importance. Hence, 4D flow MRI may be an alternative for assessing the hemodynamics of AVFs. Purpose To compare the hemodynamics of AVFs using Doppler ultrasound (DUS) and 4D‐MRI in renal dialysis patients. Study Type Case–control study from October 2017 to April 2018. Population Fifty patients (age [range] = 59.52 [39–71] years) with AVFs were included. Field Strength/Sequence Black‐blood MRI and 4D flow MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…21 In recent years, some studies have shown that 4D flow MRI is a promising technique for noninvasive estimation of AVF hemodynamics. 22 In this study, 4D-flow MRI was used to visualize and quantify the hemodynamics of AVF created by MNTT. Multidirectional flow, as characterized by medium or high the time-averaged WSS (Figure 3(a) and (b)) was located on the inner wall of the radial artery, the anastomosis floor (except the heel), and on the anterior wall of cephalic vein near the anastomosis floor.…”
Section: Discussionmentioning
confidence: 99%
“…21 In recent years, some studies have shown that 4D flow MRI is a promising technique for noninvasive estimation of AVF hemodynamics. 22 In this study, 4D-flow MRI was used to visualize and quantify the hemodynamics of AVF created by MNTT. Multidirectional flow, as characterized by medium or high the time-averaged WSS (Figure 3(a) and (b)) was located on the inner wall of the radial artery, the anastomosis floor (except the heel), and on the anterior wall of cephalic vein near the anastomosis floor.…”
Section: Discussionmentioning
confidence: 99%
“…4D flow is another option available with MRI, which provides the ability to assess flow, pressure, and wall shear stress. Suqin et al showed that 4D flow MRI velocities and flow volumes have moderate agreement with ultrasound values and specific hemodynamic parameters are associated with AVF maturation and complications ( 44 ).…”
Section: Imaging Evaluation Of Avfs and Avgsmentioning
confidence: 99%